2011
DOI: 10.1155/2011/818291
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cell Carcinoma of the Nipple: An Uncommon but Ever-Increasing Location

Abstract: Basal cell carcinoma (BCC) is the most common malignancy of the skin. It is most frequently seen on the sun-exposed areas of the head and neck region. Occurrence of BCC on the nipple is extremely rare, though the number of the reported cases has been increasing steadily. It has metastatic potential to regional lymph nodes; therefore a more aggressive course can be expected when compared to BCCs located at other sites. Hence, early diagnosis and treatment of BCCs located on this region is of importance. There a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Irregular proliferation of basaloid cells attached to the epidermis and peritumoral retraction clefts are the typical features for BCC-NAC, but not for other differential diseases including breast eczematous conditions, seborrheic keratosis, pigmented Bowen’s disease, pigmented mammary Paget’s disease, and superficial spreading melanoma 6910…”
Section: Discussionmentioning
confidence: 99%
“…Irregular proliferation of basaloid cells attached to the epidermis and peritumoral retraction clefts are the typical features for BCC-NAC, but not for other differential diseases including breast eczematous conditions, seborrheic keratosis, pigmented Bowen’s disease, pigmented mammary Paget’s disease, and superficial spreading melanoma 6910…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous BCC involving the nipple is rare but numerous reports exist, some suggesting a male predominance. [22][23][24][25] Importantly, several studies suggest an increased incidence of metastases for BCC of the nipple; as a result, SLN biopsies are performed in some patients with nipple BCC. [26][27][28][29] Cutaneous BCC may display many growth patterns including buds of basaloid epithelium at the base of the epidermis, tumor cell nodules of varying size, or trabecular aggregates of tumor cells dissecting through the collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that ultraviolet (UV) irradiation might be a causal factor in BCC of the NAC. Three out of six cases (50 %) of BCC of the NAC with multiple lesions had a history of extensive sun exposure (Table 1) [7][8][9]. Considering that the five BCCs and one SCC in our patient had only developed in areas previously irradiated, radiation therapy was thought to be the most likely cause in the present case.…”
mentioning
confidence: 92%